Effects of an In-home Multicomponent Exergame Training on Physical Functions, Cognition, and Brain Volume of Older Adults: A Randomized Controlled Trial - Adcock, Manuela; Fankhauser, Mélanie; Post, Jennifer; Lutz, Kai; Zizlsperger, Leopold; Luft, Andreas R.; Guimarães, Vânia; Schättin, Alexandra; de Bruin, Eling D. (Frontiers in Medicine, 2020)
Aging is associated with a decline in physical functions, cognition and brain structure. Considering that human life is based on an inseparable physical-cognitive interplay, combined physical-cognitive training through exergames is a promising approach to counteract age-related impairments. The aim of this study was to assess the effects of an in-home multicomponent exergame training on [i] physical and cognitive functions and [ii] brain volume of older adults compared to a usual care control group. Thirty-seven healthy and independently living older adults aged 65 years and older were randomly assigned to an intervention (exergame training) or a control (usual care) group. Over 16 weeks, the participants of the intervention group absolved three home-based exergame sessions per week (à 30-40 minutes) including Tai Chi-inspired exercises, dancing and step-based cognitive games. The control participants continued with their normal daily living. Pre- and post-measurements included assessments of physical (gait parameters, functional muscle strength, balance, aerobic endurance) and cognitive (processing speed, short-term attention span, working memory, inhibition, mental flexibility) functions. T1-weighted magnetic resonance imaging was conducted to assess brain volume. Thirty-one participants (mean age = 73.9 ± 6.4 years, range = 65 – 90 years, 16 female) completed the study. Inhibition and working memory significantly improved post-intervention in favour of the intervention group (inhibition: F(1) = 2.537, p = .046, n2p = .11, working memory: F(1) = 5.872, p = .015, n2p = .02). Two measures of short-term attentional span showed improvements after training in favor of the control group (F(1) = 4.309, p = .038, n2p = .03, F(1) = 8.504, p = .004, n2p = .04). No significant interaction effects were evident for physical functions or brain volume. Both groups exhibited a significant decrease in gray matter volume of frontal areas and the hippocampus over time. The findings indicate a positive influence of exergame training on executive functioning. No improvements in physical functions or brain volume were evident in this study. Better adapted individualized training challenge and a longer training period are suggested. Further studies are needed that assess training-related structural brain plasticity and its effect on performance, daily life functioning and healthy aging.